A randomized multicenter clinical trial of 99Tc‐methylene diphosphonate in treatment of rheumatoid arthritis. (3rd February 2017) - Mu, Rong; Liang, Jun; Sun, Lingyun; Zhang, Zhuoli; Liu, Xiangyuan; Huang, Cibo; Zhu, Ping; Zuo, Xiaoxia; Gu, Jieruo; Li, Xiangpei; Li, Xingfu; Liu, Yi; et al.
Abstract: Aim: To investigate the efficacy and safety of technetium‐99 conjugated with methylene diphosphonate ( 99 Tc‐MDP, Yunke Pharmaceutical industry) in the treatment of rheumatoid arthritis (RA). Methods: A total of 120 patients with active RA were randomly divided into three groups: Group A (receiving oral meloxicam tablets); Group B (receiving intravenous drip of 99 TC‐MDP); Group C (receiving combination treatment of intravenous drip of 99 Tc‐MDP and oral meloxicam tablets). The main clinical and laboratory parameters were evaluated at baseline and after 14 days of therapy. Results: After 14 days of treatment, American College of Rheumatology 20 response was 15.62%, 34.04% and 48.78% in the three groups, respectively. The incidence of adverse events in three groups were 3.13%, 8.51% and 9.76% respectly, and has no significant difference. In addition, biochemical markers of bone metabolism including bone alkaline phosphatase (BAP), tartrate resistant acid phosphatase (TRAP) and dickkopf‐1 (DKK‐1), all improved in the three groups, although more significant in Group B than Group A, and more significant in the combination group than monotherapy groups. Conclusion: 99 Tc‐MDP has good efficacy and safety in the treatment of active RA patients; the benefit was more remarkable when 99 Tc‐MDP was combined with NSAIDs. 99 Tc‐MDP may also have potential to improve bone metabolism.